MODEL PREDICTIVE CONTROL DESIGN OF PALM KERNEL SHELL GASIFICATION SYSTEM FOR HYDROGEN PRODUCTION - HUSSAIN, MAHAM (2021)
In a biomass gasification process, the bio-hydrogen gasifier is one of the most important processing units. The gasifier performance is influenced by many factors, especially the operational conditions; such as temperature, equivalence ratio (e.g. steam-to-biomass or air-to-biomass etc), as well as the choice of gasifying agent and the chemical and physical properties of the biomass. Variations in the feedstock is another key factor that affect the gasifier performance.